Sosialisasi Peningkatan Kesadaran Hukum Siswa Tentang Cyberbullying di SMP Sriwedari Malang - Purborini, Vivi Sylvia; Novitasari, Rika; Aini, Vivi Fauziatul; Santa, Maria Angelina (Abdimas Indonesian Journal, 2025)
Cyberbullying or intimidation in cyberspace has become an increasingly disturbing phenomenon in the current digital era. With increasingly widespread access to online platforms, these actions threaten the emotional well-being of individuals, especially young people. This service reviews the negative impact of cyberbullying on the victim's mental health, such as stress, anxiety, depression, and even the potential for suicide, increasing legal awareness regarding cyberbullying both in civil aspects and statutory regulations. Factors such as anonymity and the vast reach of the internet complicate prevention efforts. Therefore, there is a need for cooperation between parents, educators and online platforms in creating a safe and educational environment for users, as well as implementing stricter regulations to protect individuals from the negative impacts of cyberbullying. This activity aims to provide outreach regarding cyberbullying. The methods used are field surveys, outreach and evaluation. It is hoped that the results of this outreach activity will increase legal awareness. Socialization about cyberbullying at Sriwedari Malang Middle School is an important step to equip students with the understanding and skills needed to deal with cyberspace wisely and responsibly.